The relationship between specialised techniques and their application in practical assessments in a professionally orientated higher education programme in South Africa - Pike, Jonathan (School of Education, 2026)
This research focusses on how knowledge is represented in a professionally orientated threeyear Diploma programme in Sound Technology and Production. The programme is intended to produce graduates who are workplace ready sound engineers for the local and international audio industry. The research is intended to contribute to understanding knowledge practices in practically orientated curricula, and how these curricula prepare practitioners for employment. The research is based on an analysis of selected assessment briefs provided to the students from three modules in the programme. This data has been analysed by operationalizing the concepts of Legitimation Code Theory (LCT) – Semantics as theorised by Karl Maton. Specifically, the data has been analysed in terms of how closely the specialised techniques taught in the programme are linked to the context of their application in practice (semantic gravity), as well as how knowledge is represented in terms of its complexity (semantic density) through the three years of the programme. LCT – Semantics has been operationalised for the purposes of this research by linking the concepts of semantic gravity to Bloom's Taxonomy of Learning Outcomes, and semantic density to Biggs's SOLO taxonomy. The findings of this research show that curricula with professional or vocational modalities, such as diploma programmes, tend to exhibit both strong semantic gravity and strong semantic density, as discussed by Suellen Shay (2016). The findings also support the value of practical curricula and their knowledge practices.